Oposisi dalam Novel Hujan Bulan Juni Karya Sapardi Djoko Damono (Kajian Intertekstual Julia Kristvea) - Riski Rahmadani Miharja; Nensilianti Nensilianti; Faisal Faisal (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract.This research is an approach to the text in the novel Rain in June using Julia Kristeva's intertextual theory. The purpose of this study is to describe the opposition in the novel, which leads to traditional opposition and belief opposition. Opposition according to Julia is something that cannot be exchanged and absolutely between two competitive groups, never harmonious, never complementary, and never able to be reconciled. Through the novel Hujan Bulan Juni, Sapardi Djoko Damono, the author examines and describes how a sense of ethnic ownership can create unfriendliness between other tribes, which can be observed through the traditional opposition in the study of this novel. The results of this study are as follows: the opposition between the traditions of the Menado and Javanese tribes makes us aware that each tribe has its own uniqueness and strengths; the things that distinguish us do not necessarily become divisions within a country. The opposition to belief in this novel shows that religious people still often discriminate against each other. Basically, religion makes us as human beings who are guided by and have empathy for fellow human beings, not the other way around. The characters in this novel often question a person's religion when it is felt that he is not in line with his beliefs. The oppositions in this novel are still numerous and often occur in real life.Keywords: Opposition, Culture, Belief